Panduratin A induces protective autophagy in melanoma via the AMPK and mTOR pathway - Lai, Siew Li; Mustafa, Mohd Rais; Wong, Pooi Fong (Elsevier, 2018)
Background: Targeting autophagy is emerging as a promising strategy in cancer therapeutics in recent years. Autophagy can be modulated to drive cancer cell deaths that are notoriously resistant to apoptotic-inducing drugs. In addition, autophagy has been implicated as a prosurvival mechanism in mediating cancer chemoresistance. Our previous study has demonstrated that Panduratin A (PA), a plant-derived active compound exploits ER-stress-mediated apoptosis as its cytotoxic mechanism on melanoma. Purpose: Our previous proteomics analysis revealed that treatment with PA resulted in the upregulation of an autophagy marker, LC3B in melanoma cells. Therefore, the present study sought to investigate the role of PA-induced autophagy in melanoma cells. Methods: Transmission electron microscopy was performed for examination of autophagic ultra-structures in PA-treated A375 cells. Cytoplasmic LC3B and p62/SQSMT1 punctate structures were detected using immunofluorescene staining. Expression levels of LC3B II, p62/SQSMT1, ATG 12, Beclin 1, phospho S6 (ser235/236), phospho AMPK (Thr172) and cleaved PARP were evaluated by western blotting. Results: Autophagosomes, autolysosomes and punctuates of LC3 proteins could be observed in PA-treated A375 cells. PA-induced autophagy in A375 melanoma cells was found to be mediated through the inhibition of mTOR signaling and activation of AMPK pathway. Furthermore, we showed that PA-induced apoptosis was increased in the presence of an autophagy inhibitor, signifying the cytoprotective effect of PA-induced autophagy in melanoma cells. Conclusion: Taken together, results from the present study suggest that the inhibition of autophagy by targeting mTOR and AMPK could potentiate the cytotoxicity effects of PA on melanoma cells.